2013
DOI: 10.3844/ajassp.2013.139.146
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Estimating Portfolio Performance of Bangladesh Stock Market

Abstract: Capital Asset Pricing Model (CAPM) is one of the most important developments in the finance literature. Simply, CAPM is a model that describes the relationship between risk and expected return. The theoretical validity of CAPM is well tested and accepted but the practical validity of CAPM is in questioned. This study is designed to analyze and estimate the portfolio performance of Bangladesh stock market in a CAPM framework. For this study, monthly stock returns from 80 companies for the period of January 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Hasan et al (2013) examine and conclude that the "expected return-beta" relationship is linear in portfolios and unique risk has no effect on the expected return of portfolios. Köseoğlu and Mercangoz (2013) also conclude that the standard CAPM as well zero-beta CAPM are correspond to the expected returns of Istanbul Stock Exchange, Turkey.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Hasan et al (2013) examine and conclude that the "expected return-beta" relationship is linear in portfolios and unique risk has no effect on the expected return of portfolios. Köseoğlu and Mercangoz (2013) also conclude that the standard CAPM as well zero-beta CAPM are correspond to the expected returns of Istanbul Stock Exchange, Turkey.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Adedokun and Olakojo [32] arrived at the same results by testing monthly stock returns from a hundred Nigerian firms between January 2008, and December,2009. Hasan et al [33] tested CAPM for the Bangladesh stock market and found out that this model does not prove its validity.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…There have been many research papers supporting the effectiveness of the CAPM model's results in predicting stock returns. Besides, the limitations of CAPM was pointed out in several studies when CAPM was only based on market risk to predict stock required returns comparing with other risks or model, including the studies of Basu [7], Rosenberg, Reid and Lansten [8], Bhandari [9], Hasan Kamil, Mustafa and Baten [10], Zainul & Shintabelle Restiyanita [11], Janata [12], Matteo [13] ,Laura & Fahad [14], Lu [15], Offiong [16], Leslaw [17], Rojo-Suárez & Alonso-Conde [18]. The measurement of stock return based on only one risk variable, market risk according to CAPM, is not correct and not enough basis.…”
Section: Literature Reviewsmentioning
confidence: 99%